Springer handbook of condensed matter and materials data - Martienssen, W.; Warlimont, Hans 1931-.; Gale Group (Heidelberg, Germany Springer, 2005)
This handbook provides a concise compilation of data and functional relationships from the fields of solid-state physics and materials. It is designed to be useful as a desktop reference for fast and easy retrieval of essential and reliable data in the lab or office. Physicists, chemists, and engineers engaged in fields of solid-state sciences and materials technologies in research, development, and application will find this information very useful.
Part 1: General tables -- Part 2: The elements -- Part 3: Classes of materials -- Part 4: Functional materials -- Part 5: Special struct ures.
Electronic reproduction.
Keywords: Condensed matter -- Handbooks, manuals, etc; Electronic books